The Relationship between Perceived Workload and Organizational Justice Toward Nurses’ Intention to Leave their Profession - Agustin, Ratna; Ananditha, Aries Candra; Andy Rias, Yohanes; Thongsalab, Jutharat (Fakultas Ilmu-ilmu Kesehatan, 2022)
Perceived workload and organizational justice are significantly correlated with nurses’ intention to leave. However, limited studies have used a large sample to investigate this association. Therefore, this study aims to identify the association between perceived workload and organizational justice on nurses’ intention to leave. A cross-sectional online survey was conducted among 278 nurses by the simplified snowball sampling technique method from five hospitals in Surabaya, East Java Province, Indonesia. Adjusted odds ratios (AORs) and multiple linear regression were employed for data analysis. Perceived workload had increased intention to leave by 0.251-fold (95% CI = 0.20 to 0.31; p = <0.001). In addition, individuals with a high score of organizational justice are negatively associated with intention to leave -0.144 (95% CI = -0.19 to -0.10; p = <0.001) after the covariate variable has been adjusted. This study found a significant independent correlation between perceived workload and organizational justice toward nurses’ intention to leave. This suggests that nurses are more likely to consider leaving their jobs when they perceive a more significant workload and receive less organizational justice through policies and practices that intend to replenish resources.